If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = -7 + 3n Solving 17 = -7 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 17 + -3n = -7 + 3n + -3n Combine like terms: 3n + -3n = 0 17 + -3n = -7 + 0 17 + -3n = -7 Add '-17' to each side of the equation. 17 + -17 + -3n = -7 + -17 Combine like terms: 17 + -17 = 0 0 + -3n = -7 + -17 -3n = -7 + -17 Combine like terms: -7 + -17 = -24 -3n = -24 Divide each side by '-3'. n = 8 Simplifying n = 8
| x^3-2x=5 | | 9+7=n | | 2*(3x+4)=8*(2x-4) | | (3x^2+x+1)+(2x^2-3x-5)= | | 6z-3=z+7 | | (3y+7)=4 | | 8x+3=-9x-5 | | 6x+131=3x+184 | | 0.75y+9=0.5 | | 4c^3+4c^2-24=0 | | a^2+6a-63=0 | | p(t)=-2t^2+48t+30 | | 9x-3-4x=x+8+x | | 7(2x)-(10-3x)= | | p(t)=-2t+48t+30 | | h=vt-gt | | 6x-2-2x=x+7+x | | 15(-42x-40)=15(-8x+244) | | 8x=2-x^2 | | 6(x-7)+3(x+14)+2(x-15)=-9(x-4)+3(x+7) | | 9-6x=-4x+7 | | 4.8+10m=8.53 | | -11-5r=-8(5r-3) | | 31e=102 | | 5x^2+40=30x | | -18=16 | | -11=-45r-3 | | 63x=8p-14 | | 6x-6-3x=x+5+x | | 9a+2b+8a+3b= | | 19z=38 | | 19z=28 |